Recent notes on the avifauna of Kalimantan - Derek A Holmes; K Burton (Indonesian Ornithologists’ Union, 1987)
In the introduction to his Annotated checklist of the birds of Borneo, Smythies (1957) outlines the history of ornithological study on the island. A notable lack of field studies in Kalimantan (Indonesian Borneo) is apparent over the past fifty years. In the previous century, there had been some two dozen individuals collecting or studying, especially in the Banjarmasin area, but faunal studies virtually ceased after the outbreak of the Second World War. Pfeffer (1960-1961) took part in a French expedition to East Kalimantan, and Pearson (1975) published a brief list of birds in the Kutai reserve, the site of a field research station until it was destroyed by fire in 1983. Their data, and some unpublished records of a few others in the 1970's (J. T. Marshall, K. V. Thompson) are incorporated into the third edition of Smythies' The Birds of Borneo (1981). The purpose of the present paper is to publish notes on Kalimantan birds to cover the period from those included in the latest edition of Smythies' work up to the present time, and thus to update the record in expectation of an increase in ornithological activity in the near future. There has been very little further study, and in acknowledgement to Smythies' third edition, the Earl of Cranbook writes: “I regret only that the book still retains such a strongly northern and north-western bias. The four provinces of Kalimantan encompass the greater part of the island of Borneo. Up-to-date ornithological knowledge of this area is sadly deficient, perhaps this edition will find its way into Indonesia and stimulate interest and comment”. The present paper contributes a little to redress this imbalance.